2022
DOI: 10.1021/acsami.2c05724
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Multiple Hydride Donor To Achieve an n-Doped Polymer with High Solvent Resistance

Abstract: The ability to insolubilize doped semiconducting polymer layers can help enable the fabrication of efficient multilayer solution-processed electronic and optoelectronic devices. Here, we present a promising approach to simultaneously n-dope and largely insolubilize conjugated polymer films using tetrakis­[{4-(1,3-dimethyl-2,3-dihydro-1H-benzo­[d]­imidazol-2-yl)­phenoxy}­methyl]­methane (tetrakis-O-DMBI-H), which consists of four 2,3-dihydro-1H-benzoimidazole (DMBI-H) n-dopant moieties covalently linked to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…19−22 We have recently reported that the tetrafunctional n-dopant tetrakis[(4-(1,3-dimethyl-2,3-dihydro-1Hbenzo[d]imidazol-2-yl)phenoxy)methyl]methane largely insolubilizes a thiophene-fused benzodifurandione-based oligo(pphenylenevinylene)-co-thiophene polymer in the original deposition solvent and have attributed this to the network of electrostatic interactions formed by the resulting tetracation and negatively charged polymer chain segments. 23 Here, we focus on the two above-mentioned mechanisms for enhancing the resistance of doped polymer layers against exposure to solvent, while also retaining the dopants: preaggregation-induced and cross-linking-induced layer retention are compared to clarify the interplay of these effects and to show their potential for the fabrication of multi-heterolayer structures. First, using 1,2,4,5,7,8-hexafluoro-11,11,12,12-tetracyanonaphtho-2,6-quinodimethane (F 6 TCNNQ) as a molecular p-dopant, we show that the layer retention of P3HT can For the cross-linking approach, we use the photo-activated CLA benzene-1,3,5-triyl tris(4-azido-2,3,5,6-tetrafluorobenzoate).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19−22 We have recently reported that the tetrafunctional n-dopant tetrakis[(4-(1,3-dimethyl-2,3-dihydro-1Hbenzo[d]imidazol-2-yl)phenoxy)methyl]methane largely insolubilizes a thiophene-fused benzodifurandione-based oligo(pphenylenevinylene)-co-thiophene polymer in the original deposition solvent and have attributed this to the network of electrostatic interactions formed by the resulting tetracation and negatively charged polymer chain segments. 23 Here, we focus on the two above-mentioned mechanisms for enhancing the resistance of doped polymer layers against exposure to solvent, while also retaining the dopants: preaggregation-induced and cross-linking-induced layer retention are compared to clarify the interplay of these effects and to show their potential for the fabrication of multi-heterolayer structures. First, using 1,2,4,5,7,8-hexafluoro-11,11,12,12-tetracyanonaphtho-2,6-quinodimethane (F 6 TCNNQ) as a molecular p-dopant, we show that the layer retention of P3HT can For the cross-linking approach, we use the photo-activated CLA benzene-1,3,5-triyl tris(4-azido-2,3,5,6-tetrafluorobenzoate).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Jacobs et al observed doping-induced layer retention in a wide range of solvents for poly­(3-hexylthiophene-2,5-diyl) (P3HT) sequentially doped with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F 4 TCNQ) . Other studies on P3HT doped with tris­(pentafluorophenyl)­borane (BCF), F 4 TCNQ-doped poly­[2,5-bis­(3-dodecyl-2-thienyl)-thieno­(3,2- b )­thiophene] (C12-PBTTT), and poly­[2-methoxy-5-(2′-ethylhexyloxy)- p -phenylene vinylene] (MEH-PPV) have found aggregation of polymer chains already in solution after adding the molecular dopant to the polymer solution. We have recently reported that the tetrafunctional n-dopant tetrakis­[(4-(1,3-dimethyl-2,3-dihydro-1 H -benzo­[ d ]­imidazol-2-yl)­phenoxy)­methyl]­methane largely insolubilizes a thiophene-fused benzodifurandione-based oligo­( p -phenylenevinylene)- co -thiophene polymer in the original deposition solvent and have attributed this to the network of electrostatic interactions formed by the resulting tetracation and negatively charged polymer chain segments …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported simultaneous n-doping, insolubilization, and dopant immobilization in a conjugated polymer using postfilm-deposition thermal activation of a dopant that forms a large tetracation that acts to "electrostatically cross-link" polymer chains. 10 However, the formation of covalent bonds between semiconductors and dopants, and/or between adjacent semiconductor moieties, subsequent to film formation is, in principle, a more general and reliable approach to achieving these goals. Several examples of this approach have been reported for the case of fullerene semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The use of large dopant molecules can in some cases lead to immobilization of the dopants; however, often the doped film remains substantially soluble in the types of organic solvent typically used to deposit subsequent layers. We have recently reported simultaneous n-doping, insolubilization, and dopant immobilization in a conjugated polymer using postfilm-deposition thermal activation of a dopant that forms a large tetracation that acts to “electrostatically cross-link” polymer chains . However, the formation of covalent bonds between semiconductors and dopants, and/or between adjacent semiconductor moieties, subsequent to film formation is, in principle, a more general and reliable approach to achieving these goals.…”
Section: Introductionmentioning
confidence: 99%